SEROPREVALENCIA DE Brucella sp. EN CAPRINOS DE HUAROCHIRÍ, LIMA - Rojas G., Wilder (2006)
The purpose of the present study was to determine the seroprevalence of Brucella sp. in goats from 10 districts of the Huarochirí province, Lima. Blood samples were collected from 384 female goats older than 6 months of age for the detection of antibodies against Brucella sp. using the Rose Bengal test. None of the samples resulted positive